hAssembler: A hybrid de novo genome assembly approach for large genomes - KAIRI, AMIT; MAJUMDAR, PRIYANKA GUHA; RAO, ATMAKURI RAMAKRISHNA (The Indian Journal of Agricultural Sciences, 2020)
Genome assembly is a process where large contigs and scaffolds are constructed from raw reads generated by sequencing machines. Based on the size of the generated reads they can be primarily categorized into short reads and long reads. Modern genome assemblers follow De Bruijn Graph (DBG) approach for assembly of short reads, whereas Overlap Layout Consensus (OLC) approach for assembly of long reads. For de novo genome assembly, DBG based assemblers are very efficient at repeat resolution but are computation intensive and sensitive to sequencing errors. On the other hand, OLC based assemblers are intuitive and very time efficient but not efficient at resolving repeat regions. Here, we developed an hAssembler, which leverages the advantages of both DBG and OLC approaches and compared its performance with the existing hybrid assemblers. It uses both long reads and short reads and run OLC and DBG in parallel. By using both the long and short reads, the time complexity of hAssembler was reduced considerably. The results showed that hAssembler outperformed the existing hybrid assemblers in terms of time and performance (N50) while assembling the large genomes.